Global norms, regional practices: Taste-based and statistical discrimination in German asylum decision-making - Lidwina Gundacker; Yuliya Kosyakova; Gerald Schneider (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2021)
Asylum policy-making in advanced democracies frequently faces the accusation that prejudice and stereotyping lead to erroneous decisions. The model of taste-based discrimination suggests that the biases of decision-makers or their peers against certain groups of applicants influence the evaluation of an asylum claim. Conversely, the concept of statistical discrimination implies that a dearth of information forces impartial decision-makers to resort to stereotypes. We examine both forms of discrimination, evaluating whether they shape asylum-seekers' chances to receive protection in Germany, currently a key recipient country. Our empirical examination of a representative refugee survey in Germany confirms that asylum decisions are subject to tastebased discrimination: males, Muslims, and applicants assigned to regions with a conservative population or government are less likely to obtain asylum or other forms of protection. Conforming to the theory of statistical discrimination, stereotyping against male or Muslim applicants' manifests most pronouncedly if decision-makers suffer under high workload or possess little information. However, high information costs do not alter stereotyping in more conservative regions. Altogether, our study reveals that extra-legal reasons in the form of prejudice and stereotypes considerably undermine what should be the key criterion in assessing an asylum claim: the credibility of an individual's need for protection.
urn:nbn:de:bsz:352-2-1sumrr9j5bd2v2
Keywords: F22; H83; J16; K37; K38; 320; Asylum recognition; principal-agent models; federalism; immigration attitudes; Germany; discrimination